Prehospital treatment with levetiracetam plus clonazepam or placebo plus clonazepam in status epilepticus (SAMUKeppra): a randomised, double-blind, phase 3 trial. Issue 1 (January 2016) - Navarro, Vincent; Dagron, Christelle; Elie, Caroline; Lamhaut, Lionel; Demeret, Sophie; Urien, Saïk; An, Kim; Bolgert, Francis; Tréluyer, Jean-Marc; Baulac, Michel; Carli, Pierre; ,
Summary: Background: Generalised convulsive status epilepticus (GCSE) should be treated quickly. Benzodiazepines are the only drug treatment available so far that is effective before admission to hospital. We assessed whether addition of the antiepileptic drug levetiracetam to the benzodiazepine clonazepam would improve prehospital treatment of GCSE. Methods: We did a prehospital, randomised, double-blind, phase 3, placebo-controlled, superiority trial to determine the efficacy of adding intravenous levetiracetam (2·5 g) to clonazepam (1 mg) in treatment of GCSE in 13 emergency medical service centres and 26 hospital departments in France. Randomisation was done at the Paris Descartes Clinical Research Unit with a list of random numbers generated by computer. Adults with convulsions lasting longer than 5 min were randomly assigned (1:1) by prehospital physicians to receive levetiracetam or placebo in combination with clonazepam. All physicians and paramedics were masked to group assignments. If the status epilepticus lasted beyond 5 min after drug injection, a second dose of 1 mg clonazepam was given. The primary outcome was cessation of convulsions within 15 min of drug injection. We analysed the modified intention-to-treat population that had received at least one injection of clonazepam and levetiracetam or placebo, excluding patients without valid consent and those randomised more than once. The trial is registered at EudraCT, number 2007-005782-35. Findings: Between July 20, 2009, and Dec 15, 2012, 107 patients were randomly assigned to receive placebo and 96 were assigned to receive levetiracetam. The trial was discontinued on Dec 15, 2012 when interim analysis showed no evidence of a treatment difference, and 68 patients in each group were included in the modified intention-to-treat analysis. Convulsions stopped at 15 min of drug injection in 57 of 68 patients (84%) receiving clonazepam and placebo and in 50 of 68 patients (74%) receiving clonazepam and levetiracetam (percentage difference −10·3%, 95% CI −24·0 to 3·4). Three deaths, 19 of 47 (40 %) serious adverse events, and 90 of 197 (46%) non-serious events were reported in the levetiracetam group, and four deaths, 28 of 47 (60%) serious events, and 107 of 197 (54%) non-serious events were reported in the placebo group. Interpretation: The addition of levetiracetam to clonazepam treatment presented no advantage over clonazepam treatment alone in the control of GCSE before admission to hospital. Future prehospital trials could assess the efficacy of clonazepam alone as a first-line treatment in status epilepticus and the efficacy of a second injection of clonazepam with another antiepileptic drug as second-line treatment. Funding: UCB Pharma.